2001
DOI: 10.1159/000055376
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fhit Expression Occurs in the Early Stage of Esophageal Tumorigenesis: No Correlation with p53 Expression and Apoptosis

Abstract: The FHIT gene, encompassing the FRA3B fragile site at chromosome 3p14.2, is a candidate tumor suppressor gene involved in multiple tumors, including esophageal carcinoma. We analyzed Fhit expression using an immunohistochemical method in invasive carcinoma, carcinoma in situ (CIS) and dysplasia, in paraffin sections of 75 esophageal squamous cell carcinomas (ESCs) to further elucidate the role of Fhit protein in esophageal carcinogenesis. In addition, we also examined whether Fhit expression correlated with p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…In this study, consistent with other studies (29,39,40), we have shown that FHIT is down-regulated early during carcinogenesis and that its down-regulation is associated with increasing dysplasia grade in POLs. In addition, the loss of FHIT expression was observed more frequently in precursor lesions that developed invasive SCC.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, consistent with other studies (29,39,40), we have shown that FHIT is down-regulated early during carcinogenesis and that its down-regulation is associated with increasing dysplasia grade in POLs. In addition, the loss of FHIT expression was observed more frequently in precursor lesions that developed invasive SCC.…”
Section: Discussionsupporting
confidence: 93%
“…Alterations and abnormal transcripts of the FHIT gene have been reported in a number of primary human tumours, including CRCs (Ohta et al, 1996;Croce et al, 1999;Kitamura et al, 2001). However, some of the data are conflicting in CRCs (Hao et al, 2000;Hibi et al, 1997;Luceri et al, 2000;Mori et al, 2001;Thiagalingam et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The Fragile histidine triad (Fhit) protein has been characterised as an Ap 3 A hydrolase molecule, which cleaves the Ap 4 A substrate that may be involved in the control of DNA replication and the cell cycle (Ohta et al, 1996). Frequent abnormal transcripts were found in a variety of human cancers including those of the digestive tract, lung, breast, and head and neck (Ohta et al, 1996;Croce et al, 1999;Kitamura et al, 2001). The majority of these abnormalities include aberrant mRNA transcripts, with the absence of one or more exons within the mRNA.…”
mentioning
confidence: 99%
“…However, conflicting results from reverse transcription (RT) -PCR analysis and genomic analysis have been reported (Ohta et al, 1996;Gemma et al, 1997;Tamura et al, 1997). In general, in tumours (lung and oesophagus) associated with environmental carcinogens, alterations in the FHIT gene occur early in cancer development, but are thought to be a late event in other cancers and possibly associated with cancer progression to more aggressive neoplasia (Croce et al, 1999;Kitamura et al, 2001). Moreover, little is known about Fhit expression in early gastric neoplasia.…”
mentioning
confidence: 99%